Spectrum of magnetic resonance imaging findings of endometriosis in Kashmiri women: A Descriptive study (Journal of Pharmaceutical Negative Results, 2023)
Background: Endometriosis is a relatively common gynaecological condition affecting premenopausal women often associated with pelvic pain and infertility. It is pathologicaly characterised as the presence of ectopic endome¬trial glands and stroma outside the uterus. Because its effects may be life impacting, radiologists should be familiar with the various imaging manifestations of the disease, espe¬cially those that are relatively specific for the disease.Aims and objectives : The aim of our study is to describe the various common patterns of MRI manifestations of pelvic endometriosis in premenopausal women from Kashmir.Methodology : The current study is a cross sectional observational study conducted by reviewing already existing MRI images in the radiology department of SMHS hospital Srinagar from September 2021 to December 2022 . All the pelvic MRI studies of premenopausal females who had MRI features of endometriosis where included in the study. The MRI studies of these patients where re-evaluated and compiled by experienced radiologists with more than 8 years of experience in radiology. Exclusion criteria included a history of pelvic surgery for endometriosis or adnexal disease.Results : We gathered the imaging data from 47 patients. Out of these 27 patients had ovarian endometriosis with its varied manifestations, endometriosis associated adhesions were seen in 16 patients,14 patients had posterior cul de sac disease, anterior cul de sac involvement was seen in 7 patients. Round ligaments were involved in 7 patients, 9 patients had tubal disease. Deep pelvic endometriosis infiltrating the rectal wall was seen in 5 patientsConclusion : In our study we were able to depict the commonest MRI imaging patterns in pelvic endometriosis in Kashmiri women. Indeed MRI is able to preoperatively detect maximum endometriotic lesions thereby improving diagnostic imaging accuracy and patients’ outcome, and to reduce postoperative complication rates.